ANALISIS KETERAMPILAN TEKNIK DASAR FUTSAL PADA EKSTRAKURIKULER FUTSAL SMA SANTA MARIA NANGA PINOH KALIMANTAN BARAT - Suyatmin Suyatmin; Nur Sulistyo M; Nur Moh Kusuma Atmaja (STKIP Melawi, 2024)
Abstract: This research aims to determine the level of futsal playing skills of futsal extracurricular participants in SMA Santa Maria Nanga Pinoh, Malawi Regency. Basic technical skills for playing futsal include: passing, controlling, dribbling, and shooting. This research is quantitative descriptive research with one variable without making comparisons or connecting with other variables. The variable in this research is the basic technical skills of playing futsal. The subjects in this research were 20 futsal extracurricular participants at Santa Maria Nanga Pinoh High School, Malawi Regency. The method used is a survey and the data collection technique uses tests and measurements. In this research, the instrument used was the